2012
DOI: 10.1371/journal.pone.0049670
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cascades Driven by Tumor Necrosis Factor-Alpha Play a Major Role in the Progression of Acute Liver Failure and Its Neurological Complications

Abstract: Background/aimsAcute liver failure (ALF) due to ischemic or toxic liver injury is a clinical condition that results from massive loss of hepatocytes and may lead to hepatic encephalopathy (HE), a serious neuropsychiatric complication. Although increased expression of tumor necrosis factor-alpha (TNF-α) in liver, plasma and brain has been observed, conflicting results exist concerning its roles in drug-induced liver injury and on the progression of HE. The present study aimed to investigate the therapeutic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 38 publications
2
69
0
2
Order By: Relevance
“…Etanercept also decreased IL-6 levels in the brain, attenuated microglial activation as assessed by OX-42 immunoreactivity, and increased brain glutathione concentrations. 63 Together, these studies support the role of inflammation, whether caused by infection or as a consequence of ALF itself, as being manifest in determining the severity, progression and outcome of HE in ALF. Figure 2 The systemic inflammatory response syndrome in the outcome of hepatic encephalopathy in acute liver failure adapted from Rolando et al .…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Acutementioning
confidence: 65%
See 1 more Smart Citation
“…Etanercept also decreased IL-6 levels in the brain, attenuated microglial activation as assessed by OX-42 immunoreactivity, and increased brain glutathione concentrations. 63 Together, these studies support the role of inflammation, whether caused by infection or as a consequence of ALF itself, as being manifest in determining the severity, progression and outcome of HE in ALF. Figure 2 The systemic inflammatory response syndrome in the outcome of hepatic encephalopathy in acute liver failure adapted from Rolando et al .…”
Section: The Role Of Systemic Inflammation In Encephalopathy In Acutementioning
confidence: 65%
“…63 However, the proinflammatory response which develops as a consequence of acute liver injury is vital in initiating liver repair and regeneration and it may be detrimental to use agents targeted to key proinflammatory mediators. Moreover, as functional immunoparesis is a consistent finding in patients with ALF and CLF, 94,118,119 this could be detrimental rendering patients susceptible to bacterial and fungal infection.…”
Section: Agents Targeted To Key Pro-inflammatory Mediators and The Inmentioning
confidence: 99%
“…Treatment of ALF mice with etanercept delays the onset of severe encephalopathy while reducing the neuroinflammatory response. 62 A previous study in the same animal model showed that TNFa gene deletion likewise led to attenuation of the neurological complications. 41 As stated above, mild hypothermia and NAC both have the potential to reduce ALF-related increases of the brain production of pro-inflammatory cytokines including TNFa.…”
Section: Anti-inflammatory Strategiesmentioning
confidence: 93%
“…The "TNF theory" of HA/HE pathogenesis [8] emphasizes significant roles of TNF-α and other cytokines in HE up to the extent that these cytokines could be used as markers for encephalopathy grading [4,[9][10][11][12][13]. Obviously, TNF-α could be considered a suitable target for therapeutic intervention, however, with limited information on its responsiveness towards RSV in neuroinflammation and neuroexcitotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies have also emphasized significant involvement of TNF-α and other cytokines in HE to the extent that these cytokines could be used as markers for encephalopathy grading [4,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%